Sintesis dan Karakterisasi β-Tricalcium Phosphate dari Cangkang Kerang Hijau dengan Metode Hidrotermal - Alifia, Camilla; Az-Zahra, Kamila; Kurniati, Ely (Jurnal Ilmiah Teknik Kimia, 2025)
Green mussel shells contain high calcium oxide for the manufacture of β-Tricalcium Phosphate (β-TCP). β-TCP is used in bone, cement, and tooth repair. The synthesis of β-Tricalcium Phosphate is carried out by reacting calcium hydroxide solution with phosphoric acid using the hydrothermal method to produce materials with high crystallinity. In this study, the effect of sintering temperature and synthesis pH on β-TCP products was analyzed with variations in sintering temperature (℃) 780, 810, 840, 870, 900 and synthesis pH 6, 7, 8, 9, 10. The β-TCP product was analyzed by XRD (X-ray diffractometer) to determine the crystallinity of β-TCP. The research results obtained the highest yield value at a sintering temperature of 840°C with a synthesis pH of 8, which was 59.37% and the highest crystallinity was at a sintering temperature of 900°C with a synthesis pH of 8, which was 95.78%.